Economic and political hybridity: Patrimonial capitalism in the post-Soviet sphere - Neil Robinson (Journal of Eurasian Studies, 2013)
Hybridity in non-democratic states can be economic as well as political. Economic hybridity is produced by the same kind of pressures that create political hybridity, but the relationship between economic and political hybridity has not been as much studied by political scientists. This article uses the concept of patrimonial capitalism to look at economic hybridity, its stability and relationship to political hybridity. Using examples from Russia and other former Soviet states it argues that economic hybridity is unstable and that it has a potentially negative affect on political stability generally.